IDENTITAS BUDAYA DAN SOSIAL PADA MAKANAN KHAS DAERAH: TINJAUAN TERHADAP PERILAKU KONSUMSI MASYARAKAT MUSLIM PADA BULAN RAMADAN DI INDONESIA - Yanti Mulia Roza; Geofakta Razali; Endang Fatmawati; Syamsuddin Syamsuddin; Guntur Arie Wibowo (FEBI UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine cultural and social identities associated with regional specialties and the consumption behavior of Muslim communities in Indonesia during the month of Ramadan. This research uses a qualitative approach with descriptive methods. The results of the study show that regional specialties play an important role in the cultural and social identity of the Indonesian people, especially during the month of Ramadan. This can be seen from the consumption patterns of the people who prioritize regional specialties as the main menu when breaking the fast. In addition, regional specialties are also a medium for maintaining and developing cultural and social values that exist in society. This research also shows that cultural and social identities associated with regional specialties have influence on the consumption behavior of Muslim communities in Indonesia during the month of Ramadan. This can be seen from the tendency of people to prefer regional specialties that are in accordance with their cultural and religious values, as well as the desire to strengthen identity as part of a particular social group.